(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In the article, the creation of a mathematical model to optimize the selection of vacancies for graduates in enterprises. A graphic model of the percentage of skills and grades acquired by graduates of higher education institutions in mastering subjects based on the curriculum was created using the semantic method.